1977
DOI: 10.1111/j.1439-0450.1977.tb01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Frühstadium der Immunität nach Impfung von Ferkeln mit einer inaktivierten Aujeszkyvirus‐Vakzine

Abstract: Zusammenfassung Nach Impfung von 6–8 Wochen alten Ferkeln mit einer Aujeszkyvirus (AV)‐Vakzine, die aus Äthylenimin‐inaktivertem Virus und DEAE‐Dextran als Adjuvans bestand, konnten neutralisierende Antikörper zum ersten Mal eine Woche nach der Impfung nachgewiesen werden. Während des geprüften Zeitraumes (6 Wochen) waren die Titer relativ nieder und die Mittelwerte zeigten keinen signifikanten Anstieg oder Abfall. Im Gegensatz zur Antikörperbildung traten bei den vakzinierten Tieren nach intranasaler Testinfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In a previous publication we described that in 6 to 8 week old pigs a partial reduction of protection against challenge infection had been noticed 3 weeks after the application of a vaccine, consisting of ethylene-inactivated ADV and DEAE dextran as an adjuvant (WITTMANN and JAKUBIK, 1977). In spite of the fact that the clinical reactions in the control animals were significantly severer, we concluded from those experiments that a single vaccine dose not evoke optimal immunity and therefore a second vaccination should be recommended.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…In a previous publication we described that in 6 to 8 week old pigs a partial reduction of protection against challenge infection had been noticed 3 weeks after the application of a vaccine, consisting of ethylene-inactivated ADV and DEAE dextran as an adjuvant (WITTMANN and JAKUBIK, 1977). In spite of the fact that the clinical reactions in the control animals were significantly severer, we concluded from those experiments that a single vaccine dose not evoke optimal immunity and therefore a second vaccination should be recommended.…”
Section: Introductionmentioning
confidence: 84%
“…From these results one can conclude that the optimal time for revaccination would be 3 or 4 weeks post vacc. ; however, in a previous investigation we found that after a single vaccination the protection of the pigs against challenge infection had declined after 3 weeks (WITTMANN and JAKUBIK, 1977). Therefore, it is advisable to revaccinate 2 weeks post vacc.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Therefore, swine are de ned as the natural host of PRV. The nasal mucosa and oral cavity are the main sites of infection, and oral administration is more e cient than nasal inoculation [12]. PRV can also infect through vaginal mucosa or semen, which is the main mode of PRV transmission in wild boar herds.…”
Section: Introductionmentioning
confidence: 99%